(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Essential hypertension is associated with altered pulmonary function. Antihypertensive medication and lung function are also associated. Amlodipine (calcium channel blocker) and Atenolol (beta blocker) are commonly used antihypertensive drugs. Objective: To evaluate the effects of antihypertensive drugs on lung function status in patients with essential hypertension. Materials and Methods: This prospective observational study was carried out in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka, from July 2012 to June 2013 on 100 newly diagnosed essential hypertensive patients. Based on prescribed treatment, these study subjects were divided into two groups - B1 and B2. B1 included 50 patients who received amlodipine 5mg daily and B2 included 50 patients who received atenolol 50mg daily. Lung function tests were done in both B1 and B2 groups before taking medication, after 3 months of medication and after 6 months of medication. For assessing lung function status, Forced Vital Capacity (FVC), Forced Expiratory Volume in 1st second (FEV1) and Peak Expiratory Flow Rate (PEFR) were measured with a computer based Spirometer. Age, sex and BMI matched 50 apparently healthy normotensive subjects were also studied as control (group A). Data were compared among subjects of different groups. For statistical analysis independent sample‘t’ test and paired sample‘t’ test were performed. Results: Mean FVC, FEV1 and PEFR were significantly lower in newly diagnosed hypertensive patients in comparison with that of healthy normotensive subjects. Mean FVC, FEV1 and PEFR were found significantly higher in the group taking amlodipine for 6 months when compared to newly diagnosed hypertensive patients but lower than those of controls. In addition mean FVC and FEV1 were found significantly lower in the group taking atenolol for 6 months when compared to newly diagnosed hypertensive patients and those of controls. Conclusion: Reduced lung function occurs in newly diagnosed essential hypertensive patients which improve by treatment with amlodipine but decreases after treatment with atenolol. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 28-32